Penerapan Metode Struktur Tiga Babak dalam Penulisan Naskah pada Video Feature “Porter: Ketidakpastian yang Dikerjakan” - Tanti Nur Apriani; Kokom Komariah; Efi Fadillah (Realisasi : Ilmu Pendidikan, Seni Rupa dan Desain, 2026)
This final project was an audiovisual feature video that explored the issue of uncertainty among informal sector workers, particularly porters at train stations. The work was motivated by the limited representation of porters, despite their important role in supporting transportation services. This report aimed to explain the application of the three-act structure in scriptwriting, consisting of Act I (Set Up), Act II (Confrontation), and Act III (Resolution). The production process included pre-production, production, and post-production stages, with scriptwriting as the main focus in constructing a structured narrative. In Act I, the work introduced the station environment and the porter profession to build audience understanding. Act II developed the conflict through the portrayal of job uncertainty, income instability, and the daily life of the main subject. Act III presented a reflective conclusion through multiple perspectives and symbolic visuals. The result showed that the three-act structure effectively created a systematic narrative flow and strengthened message delivery. In conclusion, the human-interest approach combined with observational visuals effectively conveyed social realities and fostered audience empathy toward informal workers.